Silver ion post-column derivatization electrospray ionization mass spectrometry for determination of tetrabromobisphenol A derivatives in water samples. Issue 23 (13th March 2015) - Tian, Yong; Liu, Ai-feng; Qu, Guang-bo; Liu, Chun-xiao; Chen, Jian; Handberg, Eric; Shi, Jian-bo; Chen, Huan-wen; Jiang, Gui-bin
<x xml:space="preserve">Abstract</x> Six TBBPA derivatives in water samples were sensitively electrospray ionized by Ag+ post-column derivatization and directly analyzed with HPLC-MS/MS.